Emily Dickinson’s Reception in China: A Brief Overview, Part I - Wang, Baihua (The Emily Dickinson journal, 2012)
The period between the 1910s and the 1940s, which witnessed a passionate introduction of every possible kind of Western literature in China, only resulted in a few references to Dickinson. Modern Chinese literary figures who studied in Europe and in the United States in the 1910s and 1920s paid much attention to the Western New Poetry Movement and with their newly gained insights attempted to provoke a similar and simultaneous movement in China.